Partisipasi Perempuan dalam Implementasi Program Pemberdayaan Masyarakat di Kabupaten Bantul - E. Yuningtyas Setyawati; Andreas A Susanto (Balai Besar Litbang Pelayanan Kesejahteraan Sosial, 2013)
Women’s participation is an integral part of social empowerment, yet there are still problematic issues to be tackled and a lot of gaps to be filled concerning with women’s empowerment. This study aims to describe women’s participation in the stages of implementation of the social empowerment programme in Bantul regence, to explain the reasons for women’s involvement in the implementation of the programme, and to investigate factors that support and inhibit women’s empowerment. Research questions included: Why women in Bantul regency are willing to get involved in the implementation of social empowerment programme? How do these women get involved at each stage of the implementation of social empowerment programme? What are the support and inhibit factors in the process of women’s empowerment in Bantul regency? A quantitative approach in the form of embedded case study is used in this study due to its determined focus. Primary data were collected through observation, non-structured interviews, and indepth interviews. Secondary data were collected from related document such as government and NGO reports. The data for the study was analysed by following Miles and Huberman’s interactive model of data analysis (1994).This study shows that although women have been involved and participated in each stage of social empowerment programme, at earlier stage they have done so not by their own conscience but to comply with programme requirement imposed by the administrator. At later stage, their involvements can be seen as a passive participation and were based on a desire to study and to satisfy their constituents.The inhibiting factors in the process of women’s empowerment werethe internal disagreement among programme administrators; women were forced to become programme administrators; over-involvements of the government administrators; the programmes were more physical or material oriented; elitist programmes; lack of family support to women’s involvements. The factors that supported the process of women’s empowerment were the determination in applying women’s empowerment principles and the strong will to learn among the women who in charge of the programme administrators.